2018
DOI: 10.1007/s00701-018-3495-y
|View full text |Cite
|
Sign up to set email alerts
|

No correlation between radiological and clinical outcome 1 year following cervical arthrodesis

Abstract: The clinical outcome after ACDF with PEEK cages filled with demineralized bone matrix is highly satisfactory. Radiological signs of non-fusion, subsidence, and cervical alignment have no influence on clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…However, radiological ASP findings did not correlate with clinical outcomes at the last follow-up. This finding was in concordance with previously published data 19,20) .…”
Section: Discussionsupporting
confidence: 94%
“…However, radiological ASP findings did not correlate with clinical outcomes at the last follow-up. This finding was in concordance with previously published data 19,20) .…”
Section: Discussionsupporting
confidence: 94%
“…Even when the cage subsided, Opsenak et al ( 28 ) showed that subsidence had no serious influence on the clinical outcome. A number of additional trials have shown comparable results ( 2 , 30 , 31 ). In our study, the incidence of interbody fusion cage subsidence in the ZP and ST groups was 7.7% and 9.5%, respectively.…”
Section: Discussionmentioning
confidence: 80%
“…Seventeen studies focused on the safety/efficacy between different ACDF PEEK cage constructs with occasional comparisons to "routine" ACDF controls [Table 1]. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] 1]. [4] PEEK ACDF cages resulted in comparable fusion rates, the same increases in foraminal area, and similar outcomes vs. ACDF/IA.…”
Section: Methodsmentioning
confidence: 99%
“…eir various designs include; Stand Alone (SA) or Zero Profile (ZP) cages with/without screws, cages filled with demineralized bone matrix (DBM) and/or autograft, and PEEK cages coated with hydroxyapatite or titanium [Table 1]. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Here, we reviewed 17 papers comparing the relative safety/efficacy of different single to 3 and 4-level PEEK cage ACDF constructs, with select comparisons to "routine" ACDF controls (i.e. typically using iliac autograft or allograft, and plates).…”
Section: Introductionmentioning
confidence: 99%